Química mineral e estimativas de pressão e temperatura em rochas metassedimentares do grupo araxá na região de morrinhos, sul do estado de goiás - Navarro, Guillermo Rafael Beltran [UNESP]; Zanardo, Antenor [UNESP]; Da Conceição, Fabiano Tomazini [UNESP]; De Moraes, Renato; Simões, Luiz Sergio Amarante [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2011)
In the Morrinhos region, Goiás state, Brazil, the rocks of the Araxá Group have mineral assemblages related to the metamorphic peak which occurred in this region and is typical of the amphibolite facies (kyanite zone). These rocks are associated with the initial stage of the main ductile deformation that occurred in this area. Thermobarometric calculations, including the associations, garnet + plagioclase + biotite + muscovite; garnet + plagioclase +biotite + muscovite + kyanite; garnet + plagioclase + biotite + muscovite + amphibole, with quartz in excess, indicate that the metamorphic peak occurred at temperatures of approximately 610°C and pressures in the order of 10 kbar. The P-T path is probably clockwise and is in agreement with the tectonic conditions observed in collisional settings.
Mineral chemistry and pressure and temperature estimates of metasedimentary rocks of the araxá group in the region of morrinhos, South of goiás state
Keywords: Araxá Group; Goiás; Thermobarometry; amphibolite facies; barometry; ductile deformation; geochemistry; metamorphic rock; metasedimentary rock; mineralogy; P-T-t path; pressure effect; temperature effect; Brazil; Goias